2016
DOI: 10.21873/anticanres.11245
|View full text |Cite
|
Sign up to set email alerts
|

Cyclins A, B, E and p27 in Endometrial Endometrioid Adenocarcinoma

Abstract: Combining the expression level of different cyclins may be useful in determining the prognosis in endometrial cancer. Unfortunately, it remains unclear whether high p27 expression is a poor or a favorable prognostic factor. Further large-scale studies are required to assess the effects of cyclins and p27 in endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In our study, CA 125 levels of patients in advanced stages were found to be statistically significantly higher than CA 125 levels of patients in early stages (p=0.001). In addition, the fact that CA 125 levels are significantly higher in cases with greater depth of myometrial invasion shows that contrary to some studies, CA 125 levels can be used preoperatively to predict not only lymph node metastasis but also myometrial invasion 14 . Niloff and colleagues 15 These results support our results and suggest that serum CA125 levels can be used as a marker of disease spread in patients diagnosed with EC.…”
Section: Discussionmentioning
confidence: 63%
“…In our study, CA 125 levels of patients in advanced stages were found to be statistically significantly higher than CA 125 levels of patients in early stages (p=0.001). In addition, the fact that CA 125 levels are significantly higher in cases with greater depth of myometrial invasion shows that contrary to some studies, CA 125 levels can be used preoperatively to predict not only lymph node metastasis but also myometrial invasion 14 . Niloff and colleagues 15 These results support our results and suggest that serum CA125 levels can be used as a marker of disease spread in patients diagnosed with EC.…”
Section: Discussionmentioning
confidence: 63%
“…Most studies of CA-125 and EC included patients with advanced-stage disease [8][9][10] . Therefore, CA-125, as an epithelial surface antigen, can be expected to be elevated in patients with advanced-stage disease and may be associated with disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative cancer antigen-125 (CA-125) levels have also been linked to disease recurrence 7 . While an elevation in serum CA-125 levels has been found to be correlated with advanced-stage EECs, its role in early-stage EECs is still a topic of debate [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Overexpression of cyclin E has been shown to promote genomic instability by causing DNA replication stress and deregulating the G1 to S transition. [4][5][6][7][8][9][10] WEE1 kinase, which arrests cells in G2/M through inhibition of CDK1/2 to block premature mitotic entry, is essential to prevent massive DNA damage and cell death in cyclin E-overexpressed cells, [11][12][13] which can be reversed by WEE1 kinase inhibition with adavosertib, resulting in mitotic catastrophe and apoptosis induced by unrepaired DNA damage. [13][14][15][16] Laboratory studies showed that cyclin E overexpression was predictive of antitumor response to adavosertib, 17 which provided preclinical proof-of-mechanistic evidence to support the use of cyclin E as a potential biomarker of response to adavosertib.…”
Section: Introductionmentioning
confidence: 99%